BOOMING TANAMAN HIAS DI SAAT PANDEMI COVID 19, PEMODELAN DESAIN LANSKAP DI KOTA PEKALONGAN - Ari Handriatni (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2022)
In 2019, the world has experienced a COVID-19 pandemic starting from Wuhan, China. As the virus was getting worst, all of the community activity such as education, economic, and social were restricted. During this time, people have experience bored as their activities were only stay at home to prevent the spread of COVID-19. In general, to overcome this boredom, the community, especially mothers, diverts boredom by farming ornamental plants at home. There are several types of ornamental plants that are commonly planted and dominantly planted, namely Epipremnum aureum, Cactus sp., Aglaonema sp., Anthurium sp., Caladium sp., Monstera sp., Calathea sp.,Sansevierra sp., Alocasia sp., Piperomia sp., Coleus sp.. The usual ornamental plant cultivation techniques include planting plants in pots by first being given a planting medium, usually using a mixture of soil, manure and fresh husks. Ornamental plants are usually purchased in traditional markets, roadside markets or street markets. The maintenance includes watering, changing planting media, providing N, P, K fertilizer or liquid organic fertilizer, providing buffer and pruning. Modeling landscape design in arranging ornamental plants by placing vertically, hanging, stratified or pasted.